2013
DOI: 10.1111/j.1527-2001.2011.01256.x
|View full text |Cite
|
Sign up to set email alerts
|

“Nothing Short of a Horror Show”: Triggering Abjection of Street Workers in Western Canadian Newspapers

Abstract: Over the past decade, Canadian media coverage of street sex work has steadily increased. The majority of this interest pertains to graphic violence against street sex workers, most notably from Vancouver, British Columbia. In this article, the authors analyze newspaper coverage that appeared in western Canadian publications between 2006 and 2009. In theorizing the violence both depicted and perpetrated by newspapers, the authors propose an analytic framework capable of attending to the process of othering in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
0
6
0
2
Order By: Relevance
“…Hollywood representations can affect consumers' sense of identity and self (Hall, 1997;Mahtani, 2001). Women who trade sex are regularly portrayed as carriers of the disease (Hallgrimsdottir et al, 2009), social plagues (Strega et al, 2014), criminals lacking in morality who transgress norms, and/or as victims needing to be saved (Hallgrimsdottir et al, 2009;Janzen et al, 2013). Strega et al's (2014) review of sex worker depictions in Canadian media found that binary oppositions of "us" and "them" emerge through dominant portrayals of women as "vermin-victim" (p. 10).…”
Section: Methodologiesmentioning
confidence: 99%
“…Hollywood representations can affect consumers' sense of identity and self (Hall, 1997;Mahtani, 2001). Women who trade sex are regularly portrayed as carriers of the disease (Hallgrimsdottir et al, 2009), social plagues (Strega et al, 2014), criminals lacking in morality who transgress norms, and/or as victims needing to be saved (Hallgrimsdottir et al, 2009;Janzen et al, 2013). Strega et al's (2014) review of sex worker depictions in Canadian media found that binary oppositions of "us" and "them" emerge through dominant portrayals of women as "vermin-victim" (p. 10).…”
Section: Methodologiesmentioning
confidence: 99%
“…Here abjection – rejection of what is considered impure, dirty, improper, inferior, animalistic – is the process through which the ‘normal’ subject is built via the ‘abnormal’ subject. For Butler, then, the abject always produces the exclusion of certain bodies (Janzen et al, 2013). She sees abjection as a power apparatus, ‘an entire system of interrelated and organized discourses and professions, which together produce a particular truth about society and social relations’ (Janzen et al, 2013: 144).…”
Section: Abjection In Kristeva and Butlermentioning
confidence: 99%
“…For Butler, then, the abject always produces the exclusion of certain bodies (Janzen et al, 2013). She sees abjection as a power apparatus, ‘an entire system of interrelated and organized discourses and professions, which together produce a particular truth about society and social relations’ (Janzen et al, 2013: 144). This constitutes an abject body as ‘not quite’ or ‘not yet’ a person; or, in our case, not quite or not yet – or perhaps more accurately never to become – a firefighter (Butler, 1993b; Janzen et al, 2013).…”
Section: Abjection In Kristeva and Butlermentioning
confidence: 99%
“…Si las mujeres son las Otras, las prostitutas son las «Otras de las Otras». En el imaginario social y mediático sobre la prostitución, la construcción de la prostituta como la Otra no sólo se basa en la oposición entre la mujer que sigue el ideario patriarcal en el comportamiento sexual y la que no, sino también en oposiciones de clase social (Rosembergv y Andrade 1999; Andrade 2004), 2 étnicas o de procedencia nacional (Pitman 2002;Janzen et al 2013;Fong, Holroyd y Wong 2013;Stenvoll 2002;van San y Bovenkerk 2013;Ribeiro et al 2007). 3 Esto nos lleva a una reflexión sobre el propio concepto de estigma y su naturaleza interseccional.…”
Section: Introducción Las Prostitutas Como Las Otrasunclassified
“…3 Pitman (2002) y Janzen et al (2013) hacen referencia a la estigmatización de la prostituta en la prensa canadiense, no sólo por el ejercicio del trabajo sexual sino por su origen étnico, en el caso de las mujeres indígenas que ejercen la prostitución. Fong, Holroyd y Wong (2013) detectan también estigmatización en Hong Kong con las mujeres que se prostituyen procedentes de la China continental.…”
unclassified